Analyzing the quality differences between healthy and moldy cigar tobacco leaves during the air-curing process through fungal communities and physicochemical components - Fu, Kejian; Song, Xueru; Cui, Yonghe; Zhou, Qi; Yin, Yuming; Zhang, Jilai; Zhou, Hongyin; Su, Youbo (Frontiers in Microbiology, 2024)
High-throughput Illumina sequencing technology and continuous flow analysis were employed to explore the impact of mold infestation on the quality and fungal community dynamics of cigars during air-curing. The differences between the microbial flora and physicochemical compositions of moldy (MC) and healthy (MC) tobacco leaves were analyzed, revealing significant disparities between the two groups.Aspergillus spp. represented the dominant mold in MC, with nine out of twelve isolated molds showing higher quantities on MC than on HC. Mold contamination notably decreased the total nitrogen (TN), total phosphorus (TP), total alkaloids (TA), starch, protein, and flavor constituents while increasing the total fatty acid esters (TFAA), which was accompanied by a shift towards weakly acidic pH in the leaves.Fungal community analysis indicated a significant reduction in the fungal operational taxonomic unit (OUT) numbers and diversity indices in MC, contrasting with the bacterial trends. Aspergillus exhibited significantly higher relative abundance in MC, with LEfSe analysis pinpointing it as the primary driver of differentiation. Furthermore, significant negative correlations were observed between Aspergillus and TP, starch, TA, and protein, while a significant positive association was evident with TFAA. Network analysis underscored the pivotal role of Aspergillus as the species influencing disparities between HC and MC, with its abundance serving as a critical determinant during the air-curing process. This study elucidated substantial quality distinctions between MC and HC during air-curing, with Aspergillus emerging as the key species contributing to leaf mold.